The Reform of the Academic Profession in South Africa in the Context of Historical Legacies and Global Pressures - Beverly Thaver (Les éditions de la Maison des sciences de l'Homme, 2006)
The first decade of democracy in South Africa is marked by the establishment of several policy reforms within the higher education sector as a way of redressing the legacy of the past. As a consequence of this, the shape of the academic profession is also being challenged to transform its profile into one that is more representative of a diverse democracy. In light of this, a key policy mechanism is the democratic state's employment equity mandate that has to be discharged by institutions. Effectively, this article focuses on how academics respond to the dynamics associated with the implementation of such a systemic reform at the levels of both recruitment and research practices. In this process, the article also identifies the relationship between these structural practices and the (national) historical legacy as well as the extent to which this relationship is simultaneously delimited by pressures placed on universities globally